Keramik och identitet i förromersk järnålder - Ragnesten, Ulf (In Situ Archaeologica, 2012)
Ceramics reflect the archaeological context, not only chronology. Individual identity and group identity can also be demonstrated. Through analysis of the manufacturing process, the archaeologist can form a picture of how people in ancient society regarded the relationship between man and ceramics. The article presents a hypothesis about how the people during the early Iron Age related ceramic vessels to the human body as a metaphor. The starting point is the findings from an excavation in the autumn of 2010 at Änghagen in Torslanda, Gothenburg municipality. The use of ceramics in the graves indicates that it is highly likely that female fertility in the sense of rebirth played a crucial role in the symbolism surrounding burial containers and other objects of clay. In a context of variables, the use of pottery in the burial context was linked to the identity of both the individual and the group. Analogies with the findings from the Torslanda excavation were retrieved from other parts of western Sweden as well as from Denmark. The cultural contacts between western Sweden and Jutland are apparent when comparisons are made of pottery and other grave finds, especially with regard to this burial ground.